Functional status of adults undergoing orotracheal intubation at discharge from the Intensive Care Unit (Research, Society and Development, 2025)
Patients admitted to intensive care units undergo a series of invasive treatments, bed rest, and the systemic inflammatory response of the underlying disease, and are susceptible to musculoskeletal changes and reduced functionality. This study aimed to assess the functional status of young adults who underwent orotracheal intubation upon discharge from intensive care. This is a cross-sectional, quantitative, observational, and field research study with an applied purpose. Patients aged 18 to 44 years who remained in the ICU for more than 72 hours were included. Sociodemographic data, history of current illness and clinical evolution in the ICU, mobility assessment (ICU Mobility Scale), functional assessment (Functional Independence and Measurement), assessment of peripheral muscle strength (Medical Research Council), and assessment of respiratory muscle strength (manovacuometry) were collected. The sample consisted of 9 individuals with a mean age of 28 years, 88.9% of whom were male. The average length of stay in the ICU was 17.7 days, and they were intubated for an average of 12.9 days. The results of the peripheral muscle strength scale showed that 100% had a diagnosis of muscle weakness acquired in the ICU. It was observed that 77.8% had changes in the respiratory muscles through MIP values, and 88.9% had MEP values below normal. It was also possible to observe changes in functionality in 78.8% of the participants. The results indicated satisfactory mobility, where the majority were able to walk with or without assistance. Finally, it was observed that even with peripheral and respiratory muscle weakness, and changes in functionality, the mobility of the participants was preserved.